HPMA-Based Copolymers Carrying STAT3 Inhibitor Cucurbitacin-D as Stimulus-Sensitive Nanomedicines for Oncotherapy - Tavares, Marina R; Hrabánková, Klára; Konefał, Rafał; Kaňa, Martin; Říhová, Blanka; Etrych, Tomáš; Šírová, Milada; Chytil, Petr (Pharmaceutics, 2021)
The study describes the synthesis, physicochemical properties, and biological evaluation of polymer therapeutics based on N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers intended for a tumor-targeted immuno-oncotherapy. Water-soluble linear and cholesterol-containing HPMA precursors were synthesized using controlled reversible addition-fragmentation chain transfer polymerization to reach molecular weight Mn about 2 × 104 g·mol-1 and low dispersity. These linear or self-assembled micellar conjugates, containing immunomodulatory agent cucurbitacin-D (CuD) or the anticancer drug doxorubicin (Dox) covalently bound by the hydrolytically degradable hydrazone bond, showed a hydrodynamic size of 10-30 nm in aqueous solutions. The CuD-containing conjugates were stable in conditions mimicking blood. Importantly, a massive release of active CuD in buffer mimicking the acidic tumor environment was observed. In vitro, both the linear (LP-CuD) and the micellar (MP-CuD) conjugates carrying CuD showed cytostatic/cytotoxic activity against several cancer cell lines. In a murine metastatic and difficult-to-treat 4T1 mammary carcinoma, only LP-CuD showed an anticancer effect. Indeed, the co-treatment with Dox-containing micellar polymer conjugate and LP-CuD showed potentiation of the anticancer effect. The results indicate that the binding of CuD, characterized by prominent hydrophobic nature and low bioavailability, to the polymer carrier allows a safe and effective delivery. Therefore, the conjugate could serve as a potential component of immuno-oncotherapy schemes within the next preclinical evaluation.
Keywords: cucurbitacin-D; N-(2-hydroxypropyl) methacrylamide (HPMA); immuno-oncotherapy; signal transducer and activator of transcription 3 (STAT3) inhibition; pH-controlled release